2020
DOI: 10.1053/j.jrn.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A Renal Clinician's Guide to the Gut Microbiota

Abstract: It is increasingly recognized that the gut microbiota plays a role in the progression of chronic diseases and that diet may confer health benefits by altering the gut microbiota composition. This is of particular relevance for chronic kidney disease (CKD), as the gut is a source of uremic retention solutes, which accumulate as a result of impaired kidney function and can exert nephrotoxic and other harmful effects. Kidney dysfunction is also associated with changes in the composition of the gut microbiota and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 133 publications
(144 reference statements)
1
16
0
Order By: Relevance
“…UTs are usually produced through the metabolism of amino acids by intestinal microbiota microbiota, and accumulated UTs can change the composition of intestinal microbiota. Increasing evidence shows that intestinal microbiota plays a crucial role in the development of CKD [51]. Therefore, the current methods of reducing UTs through diet control and supplement therapy include reducing protein intake through a low-protein or plantbased diet [52] and supplementing probiotics, prebiotics, and synbiotics to change the composition of intestinal microbiota; some supplements could exert anti-inflammatory and antioxidative effects [53].…”
Section: Diet Control and Diet Supplementsmentioning
confidence: 99%
“…UTs are usually produced through the metabolism of amino acids by intestinal microbiota microbiota, and accumulated UTs can change the composition of intestinal microbiota. Increasing evidence shows that intestinal microbiota plays a crucial role in the development of CKD [51]. Therefore, the current methods of reducing UTs through diet control and supplement therapy include reducing protein intake through a low-protein or plantbased diet [52] and supplementing probiotics, prebiotics, and synbiotics to change the composition of intestinal microbiota; some supplements could exert anti-inflammatory and antioxidative effects [53].…”
Section: Diet Control and Diet Supplementsmentioning
confidence: 99%
“…The uremic toxins, indoxyl sulfate (IS) and p-cresyl sulfate (PCS), have increasingly been associated with accelerated kidney disease progression and cardiovascular morbidity and mortality [3][4][5]. These toxins are produced through the metabolism of the dietary amino acids, tryptophan (IS) and tyrosine (PCS), respectively, by the gut microbiota [6]. Both IS and PCS are predominantly bound to plasma proteins, such as albumin, and rely on kidney excretion.…”
Section: Introductionmentioning
confidence: 99%
“…[ 57 ] Future studies would benefit from the use of shotgun metagenomics, to enhance the resolution of bacterial species identified and metatranscriptomics to provide greater insight into the functional impact of the microbiota. [ 58 ] Whilst the current study observed that a high protein diet was associated with renal injury, there was only a trend towards concomitant renal fibrosis. Previous animal studies that have utilized rats [ 26,27 ] and pigs [ 33 ] have observed that high protein diets are associated with an increase in glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 58%